METHODOLOGICAL PSYCHOLOGICAL INTERVENTION WITH FOOTBALL TRAINERS TO IMPROVE COACHING COMPETENCE PERCEIVED BY ATHLETES, SATISFACTION WITH COACH, ENJOYMENT AND INTENTION OF PERSISTING - Lençe Aleksovska-Velickovska; Mustafa Levent İnce; Seryozha Gontarev; Zikica Tasevski; Miodrag Todorovic (My University, 2021)
Objectives: The purpose of the study was to assess the effect of a coaching intervention on soccer athletes’ perceptions of the coaches’ competencies, enjoyment, satisfaction, and intention to persist in the sport. Equipment and methods:The research was conducted on a sample of 105 young football players aged 10 to 15, drawn from 6 clubs:FC Maribor-Slovenia, FC Pelister-Macedonia, FC GoricaCroatia, FC Graficar-Serbia, FC Doboj-BiH, FC Zeleznichar-Sarajevo. Focused on coacheffectiveness, coaches from EG received a 12-hour training program.Self-report questionnaires were administered to the athletes both at the beginning and the end of the intervention. The correlation of scales and subscales in the initial and final measurements was determined by Pearson correlation coefficients. The effects of the intervention program (differences between the initial and final measurement) were determined by ttests for dependent samples. Results: The results showed significant changes in competence for game strategy (t = 29,20; p = 000), technical competence (t = 10, 06; p = 002), character building competence (t = 9.65; p = 002) and enjoyment (t = 7.11; p = 008). Thus, these types of interventions are effective for improving and maintaining over time variables related to athletes’ perception of their coaches’ competency, enjoyment and character building competence.
Keywords: Association football, character building, coach effectiveness, motivation, youth sport